The demographic consequences of growing older and bigger in oyster populations. Issue 7 (21st September 2016) - Moore, Jacob L.; Lipcius, Romuald N.; Puckett, Brandon; Schreiber, Sebastian J.
Abstract: Structured population models, particularly size‐ or age‐structured, have a long history of informing conservation and natural resource management. While size is often easier to measure than age and is the focus of many management strategies, age‐structure can have important effects on population dynamics that are not captured in size‐only models. However, relatively few studies have included the simultaneous effects of both age‐ and size‐structure. To better understand how population structure, particularly that of age and size, impacts restoration and management decisions, we developed and compared a size‐structured integral projection model (IPM) and an age‐ and size‐structured IPM, using a population of Crassostrea gigas oysters in the northeastern Pacific Ocean. We analyzed sensitivity of model results across values of local retention that give populations decreasing in size to populations increasing in size. We found that age‐ and size‐structured models yielded the best fit to the demographic data and provided more reliable results about long‐term demography. Elasticity analysis showed that population growth rate was most sensitive to changes in the survival of both large (>175 mm shell length) and small (<75 mm shell length) oysters, indicating that a maximum size limit, in addition to a minimum size limit, could be an effective strategy for maintaining a sustainable population. In contrast, the purely size‐structured model did not detect the importance of large individuals. Finally, patterns in stable age and stable size distributions differed between populations decreasing in size due to limited local retention and populations increasing in size due to high local retention. These patterns can be used to determine population status and restoration success. The methodology described here provides general insight into the necessity of including both age‐ and size‐structure into modeling frameworks when using population models to inform restoration and management decisions.